PENGEMBANGAN OBJEK WISATA DANAU DENDAM TAK SUDAH DALAM PERSPEKTIF COLLABORATIVE GOVERNANCE - Ismail, Rahmat; Ismail, rahmat ismail; Aprianty, Henny; Noviyanto, Hernowo (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
This study aims to determine and understand the development of the Dendam Tak Sudah Lake tourist attraction in the perspective of collaborative governance. In addition, this study also aims to formulate a Collaborative Model and Process related to the Development of the Dendam Tak Sudah Lake Tourist Attraction in the Perspective of Collaborative Governance. The method used in this study is a qualitative descriptive method. Data collection techniques use observation techniques, in-depth interviews, and documentation, using Yoeti's theory of Tourism Object Development and Ansell and Gash's theory of Collaborative Governance. The technique for checking the validity of the data in this study uses triangulation techniques, in this study the triangulation used is source and technique triangulation. While the techniques used for data analysis in this study are data reduction, data presentation, and drawing conclusions and verification. The results of this study found that in the Dendam Tak Sudah Lake Tourist Attraction there are three factors that can determine the success of tourism development as an industry and although there has been progress in infrastructure after the lake was changed its status to a Nature Tourism Park, there is still an urgent need for the provision of basic facilities such as toilets and coordination between related parties